Immunoprofiling of Cell Wall Carbohydrate Modifications During Flooding-Induced Aerenchyma Formation in Fabaceae Roots - Pegg, Timothy; Edelmann, Richard R.; Gladish, Daniel K. (Frontiers in Plant Science, 2020)
Understanding plant adaptation mechanisms to prolonged water immersion provides options for genetic modification of existing crops to create cultivars more tolerant of periodic flooding. An important advancement in understanding flooding adaptation would be to elucidate mechanisms, such as aerenchyma air-space formation induced by hypoxic conditions, consistent with prolonged immersion. Lysigenous aerenchyma formation occurs through programmed cell death (PCD), which may entail the chemical modification of polysaccharides in root tissue cell walls. We investigated if a relationship exists between modification of pectic polysaccharides through de-methyl esterification (DME) and the formation of root aerenchyma in select Fabaceae species. To test this hypothesis, we first characterized the progression of aerenchyma formation within the vascular stele of three different legumes - Pisum sativum, Cicer arietinum, and Phaseolus coccineus – through traditional light microscopy histological staining and scanning electron microscopy. We assessed alterations in stele morphology, cavity dimensions, and cell wall chemistry. Then we conducted an immunolabeling protocol to detect specific degrees of DME among species during a 48-hour flooding time series. Additionally, we performed an enzymatic pretreatment to remove select cell wall polymers prior to immunolabeling for DME pectins. We were able to determine that all species possessed similar aerenchyma formation mechanisms that begin with degradation of root vascular stele metaxylem cells. Immunolabeling results demonstrated DME occurs prior to aerenchyma formation and prepares vascular tissues for the beginning of cavity formation in flooded roots. Furthermore, enzymatic pretreatment demonstrated that removal of cellulose and select hemicellulosic carbohydrates unmasks additional antigen binding sites for DME pectin antibodies. These results suggest that additional carbohydrate modification may be required to permit DME and subsequent enzyme activity to form aerenchyma. By providing a greater understanding of cell wall pectin remodeling among legume species, we encourage further investigation into the mechanism of carbohydrate modifications during aerenchyma formation and possible avenues for flood-tolerance improvement of legume crops.